Odpowiedź:
[tex]a)\ \ -2.5\cdot1\frac{1}{3}+(-\frac{1}{2})^3-5\cdot(-12)=-\frac{25}{10}\cdot\frac{4}{3}+(-\frac{1}{8})+60=-\frac{5}{\not2_{1}}\cdot\frac{\not4^2}{3}-\frac{1}{8}+60=\\\\=-\frac{10}{3}-\frac{1}{8}+60=-\frac{80}{24}-\frac{3}{24}+60=-\frac{83}{24}+60=60-3\frac{11}{24}=59\frac{24}{24}-3\frac{11}{24}=56\frac{13}{24}[/tex]
[tex]b)\ \ 5\frac{3}{5}-[(-0,1)^3-(-2\frac{3}{4})\cdot(-0,8)]+(-8\frac{1}{2})=5\frac{3}{5}-[(-\frac{1}{10})^3+\frac{11}{\not4_{1}}\cdot(-\frac{\not4^1}{5})]-8\frac{1}{2}=\\\\=5\frac{3}{5}-(-\frac{1}{1000}-\frac{11}{5})-8\frac{1}{2}=5\frac{3}{5}-(-\frac{1}{1000}-\frac{2200}{1000})-8\frac{1}{2}=5\frac{3}{5}-(-\frac{2201}{1000})-8\frac{1}{2}=\\\\=5,6+\frac{2201}{1000}-8,5=5,6+2,201-8,5=7,801-8,5=-0,699[/tex]